Fruits and vegetables for healthy diets: Priorities for food system research and action - Harris, Jody; de Steenhuijsen Piters, Bart; McMullin, Stepha; Bajwa, Babar; de Jager, Ilse; Brouwer, Inge D. (Springer, 2023)
Fruits and vegetables are vital for healthy diets, but intake remains low for a majority of the global population. This chapter reviews academic literature on food system issues, as well as opportunities for research and action, as an input into the 2021 UN Food Systems Summit in the context of the International Year of Fruits and Vegetables.